2019
DOI: 10.1128/mra.00585-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Parabacteroides distasonis Strain (CavFT hAR46) Isolated from a Gut Wall-Cavitating Microlesion in a Patient with Severe Crohn’s Disease

Abstract: Crohn’s disease (CD) is a chronic inflammatory bowel disease (IBD) of the digestive tract in humans. There is evidence that Parabacteroides distasonis could contribute to IBD. Here, we present the complete genome sequence of a strain designated CavFT-hAR46, which was isolated from a gut intramural cavernous fistulous tract (CavFT) microlesion in a CD patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 13 publications
3
42
0
Order By: Relevance
“…For example, gelatin hydrolysis and collagenase tests may suggest a lack of proteolytic activity in P. distasonis, but, as previously mentioned, we have recovered this species from micro cavitating (fistulizing) lesions in the gut wall of Crohn's disease resected bowels, supporting the potential for proinflammatory activity in IBD. 97 Additional tests and growth assays will be performed to confirm this observation. As of January 12, 2021, there are 133 genomes for P. distasonis registered in the bioinformatics resource database PATRIC ver.…”
Section: Aggravatormentioning
confidence: 87%
See 2 more Smart Citations
“…For example, gelatin hydrolysis and collagenase tests may suggest a lack of proteolytic activity in P. distasonis, but, as previously mentioned, we have recovered this species from micro cavitating (fistulizing) lesions in the gut wall of Crohn's disease resected bowels, supporting the potential for proinflammatory activity in IBD. 97 Additional tests and growth assays will be performed to confirm this observation. As of January 12, 2021, there are 133 genomes for P. distasonis registered in the bioinformatics resource database PATRIC ver.…”
Section: Aggravatormentioning
confidence: 87%
“…Nagayama et al 96 demonstrated that P. distasonis, along with nine other anaerobic bacteria cultured from the small intestinal mucosa of CD patients, enhanced T H 1 and T H 17 cell accumulation and intestinal inflammation. 96 Furthermore, we have recently identified P. distasonis in the deep-gut wall tissues from patients that underwent surgery for the removal of chronically inflamed bowel segments, specifically patients afflicted with CD, 97 supporting a probable pathologic role for this species in CD. This corroberates the observed enrichment of Bacteroidetes in the gut metagenome of the SAMP mouse line, which is naturally prone to CD-like ileitis.…”
Section: Aggravatormentioning
confidence: 93%
See 1 more Smart Citation
“…A particular strain (CavFT-hAR46) has been isolated from a gut intramural cavernous fistulous tract microlesion from the gut wall of a CD patient. The authors suggested it to be a potential pathogenic strain, however they did not demonstrate its capacity to promote intestinal inflammation [ 86 ]. Peptidoglycan recognition proteins ( Pglyrps ) have been shown to participate in maintaining intestinal microbiota and mice deficient in the encoding genes were more sensitive to colitis and presented an increased level of P. distasonis and Prevotella falsenii [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that Parabacteroides and Catenisphaera contribute to inflammatory diseases, such as inflammatory bowel disease (IBD) ( Kaakoush, 2015 ; Yang et al, 2019 ). In our study, Parabacteroides and Catenisphaera (members of the family Erysipelotrichaceae ) were markedly increased ( P < 0.01, P < 0.05, respectively) in PCV3-inoculated piglets at 14 dpi compared to sham-inoculated piglets ( Kanno et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%